Pelatihan dan keterlibatan kerja dalam meningkatkan kinerja Aparatur Sipil Negara (ASN) Fakultas Matematika Ilmu Pengetahuan Alam Universitas Sumatera Utara - Elvan Rifiyanto Pane; Muslim Wijaya (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
Preliminary; The USU Faculty of Mathematics and Science is an educational institution, to create an effective and efficient workplace, efforts are needed to achieve these goals. From the observations made, the phenomenon of problems that occur in job involvement and job training causes decreased performance. Destination; to determine the effect of training and overwork on the performance of ASN at the USU Faculty of Mathematics and Natural Sciences. Method; conducted associatively using a sample of 68 respondents. The data analysis technique used statistical analysis. The results of this study indicate that: (1) partially training in improving the performance of the State Civil Apparatus (ASN), Faculty of Mathematics and Natural Sciences, University of Sumatra North. (2) partially work involvement has an effect on improving the performance of the State Civil Apparatus (ASN), Faculty of Mathematics and Natural Sciences, University of North Sumatra (3) Simultaneously Training and work involved in improving the performance of the State Civil Apparatus (ASN), Faculty of Mathematics and Natural Sciences, University of Sumatra North.